Emerging Role for Mammalian Target of Rapamycin in Male Fertility. (March 2017) - Oliveira, Pedro F.; Cheng, C.Y.; Alves, Marco G.
Abstract : Male fertility is modulated by environmental, endocrine, paracrine, and metabolic cues. Mammalian target of rapamycin (mTOR) coordinates many cellular events in response to those signals. Here, we discuss how the mTOR pathway integrates and mediates signals throughout the male reproductive system, acting as a central player in the control of spermatogenesis.